A chemical/mineralogical investigation of the behavior of sulfoaluminate binders submitted to accelerated carbonation. (July 2018) - Gastaldi, Daniela; Bertola, Federica; Canonico, Fulvio; Buzzi, Luigi; Mutke, Sabine; Irico, Sara; Paul, Geo; Marchese, Leonardo; Boccaleri, Enrico
Abstract: The paper addresses the carbonation of CSA based binders from the mechanical, chemical and mineralogical point of view. Three different binders have been investigated, revealing that many hydrated phases can protect ettringite against carbonation. In particular, the presence of AFm phases gives a significant contribution to buffer the pH in alkaline range and to preserve the protective film of steel reinforcement bars. In a carbonated environment AFm phases act as ionic exchangers: carbonate ions replace sulfates in the interlayer and in these conditions the released sulfate ions contribute to the formation of new ettringite, with a beneficial effect on compressive strength performances. Experimental data are compared with models and carbonation mechanisms are described.